A field trial of resin-based and glass–ionomer fissure sealants: clinical and radiographic assessment of caries - Poulsen S, Laurberg L, Væth M, Jensen U, Haubek D. (Blackwell Synergy, 2006)
The purpose of the present study was to provide further data for comparison of retention and caries-preventive effect of a resin-based sealant (Delton ), and a glass–ionomer sealant (Fuji III ).